STRATEGI KOMUNIKASI BALAI TAMAN NASIONAL TESSO NILO DALAM MELESTARIKAN HUTAN KONSERVASI BERBASIS PEMBERDAYAAN MASYARAKAT DI KABUPATEN PELALAWAN - Sahrul Amal; Muhammad Firdaus; Welly Wirman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study analyzes the communication strategy of the Tesso Nilo National Park Agency (TNTN) in conserving forests threatened by encroachment, illegal logging, and human wildlife conflict. Using a descriptive qualitative method with interviews, observations, and documentation in Lubuk Kembang Bunga Village, the study examines planning, implementation, and evaluation stages. The strategy emphasizes community empowerment by involving local communities, traditional leaders, farmer groups, and women’s groups. Findings show that communication planning focused on persuasive messages, implementation included socialization, training on non-timber forest products, business mentoring, and community-based ecotourism, while evaluation was conducted through monitoring and stakeholder coordination. Overall, the strategy improved participation, reduced illegal practices, and raised collective awareness, although decision-making remains dominated by TNTN. The study concludes that effective forest conservation requires participatory communication and multi-stakeholder collaboration.